230k views
3 votes
(x-5)(3x-8)=(4-3x)(6-x)+13​

1 Answer

7 votes

Answer:

x = 3

Explanation:

Use FOIL method

(x - 5)(3x - 8) = x*3x + x*(-8) + (-5)*(3x) + (-5)*(-8)

= 3x² - 8x - 15x + 40 {Combine like terms}

= 3x² - 23x + 40

(4 - 3x)( 6 - x) = 4*6 + 4 *(-x) + (-3x)*6 + (-3x)*(-x)

= 24 - 4x - 18x + 3x² {Combine like terms}

= 3x² - 22x + 24

(x - 5)(3x - 8) = (4 - 3x)( 6 - x) + 13

3x² - 23x + 40 = 3x² -22x + 24 + 13

3x² - 23x + 40 - 3x² + 22x - 24 - 13 = 0

3x² - 3x² - 23x + 22x + 40 - 24 - 13 = 0 {Combine like terms}

0 - x = 0

-x +3= 0

3 = x

x =3

User DanielCollier
by
5.2k points